Republic of Belarus : Report on Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2004)
This report reviews the Observance of Standards and Codes on Fiscal Transparency for Belarus. Belarus meets the requirements of the fiscal transparency code in some important areas. There is a comprehensive legal and administrative framework for management of budget resources. The Budget systems law contains an explicit commitment to an open and transparent budget process, and budget coverage improved considerably with the inclusion of five major extrabudgetary funds into the budget in 1998. Budget execution mechanisms are quite effective, and budget execution reports are of consistent quality.